PERAN NEGARA DALAM MEMENUHI HAK-HAK NARAPIDANA KELOMPOK RENTAN DI SISTEM PEMASYARAKATAN - Subroto, Mitro; Waliyuddin, Zain Difa (Ensiklopedia Sosial Review, 2024)
This research examines the role of the state in fulfilling the rights of vulnerable prisoners within the correctional system. The urgency of this study arises from the increasing recognition of the need for humane treatment and protection of the rights of marginalized groups in prisons. A qualitative research method was employed, utilizing interviews and document analysis to gather data. The findings indicate that while the state has established frameworks for safeguarding prisoners' rights, significant gaps remain in their implementation, particularly for vulnerable groups such as women, the elderly, and individuals with disabilities. The study concludes that a more proactive approach is essential for the state to effectively fulfill its obligations and ensure the protection of these rights.Keywords: state role; prisoners' rights; vulnerable groups; correctional system; human rights.